A study on the relationship between inflation rate, exchange rate, interest rate and gold price towards Malaysian stock market performance / Nazatul Shahernie Azmi - Azmi, Nazatul Shahernie (Faculty of Business and Management, 2017)
The aim of this study is to investigate the relationship between interest rate, inflation rate, exchange rate, and gold price towards Malaysian stock market performance. The study used Simple Linear Regression and Multiple Linear Regression in order to find the relationship interest rate, inflation rate, exchange rate, and gold price towards Malaysian stock market performance. The data of variable is collected in quarterly from January 2000 until December 2015. From the result, it reveals that interest rate and inflation rate have a significant positive relationship towards Malaysian stock market performance. Meanwhile, changes exchange rate and gold price have no significant relationship on the changes of Malaysian stock market performances. These results further our understanding of the relationship between the interest rate, inflation rate, exchange rate, and gold price towards Malaysian stock market performance and should be useful for regulator, investor and speculator.